The Role of Language and History It forms the foundation of national identity Integration and Inclusion - Khalid, Asst.Prof.Dr. Shivan Muhammad (Sulaimani Journal for Humanities, 2025)
The subject of nationalism, national thought, and the study of its principles has become a point of interest for researchers and research centers. Language and history are considered key components in shaping the national identity of individuals from any nation. Language is one of the means of connection among the individuals of a single nation, and the power of a language is tied to the strength of its speakers. Regarding the Kurdish language and its role in uniting its speakers, it has negatively affected the formation of a unified national identity due to its division into several different local dialects. This division is attributed to its ancient roots, the geographical reality, the occupation of Kurdistan by various nations, and the absence of a unified and independent entity for the Kurds in the medieval and modern ages, resulting in their division into a number of conflicting emirates. For all these reasons, the Kurdish language has not been able to play or assume a role in unifying the Kurds, but rather has become a factor of division in shaping national identity. Similarly, regarding history, although it is one of the factors uniting the members of a single nation, Kurdish history, despite being filled with events, victories, and heroes, has become a reason for the lack of interest in a unified Kurdish history due to the absence of a unified independent Kurdish entity and its division among occupiers. This has focused attention only on the history of regions, glorifying the heroes specific to geographically defined areas without considering the broader context of Kurdish history in Greater Kurdistan. Consequently, instead of playing an important role in forming a unified national identity for the Kurds, Kurdish history has become a cause of division and fragmentation.
Keywords: nation; Kurd; language; history; unity; division